The Impact of the Implementation of the 2013 Curriculum on Laboratory Management in Wonosobo High School (Universitas Negeri Semarang, 2019)
The laboratory is an integral part of teaching and learning activities in the Curriculum 2013, which emphasizes the scientific approach. Preliminary observations indicate that laboratory management is only handled by the teacher appointed as head of the laboratory. This study aims to describe the impact of the implementation of the 2013 curriculum on laboratory management. This research is expected to give a real picture of the impact of the implementation of the 2013 curriculum on laboratory management in Wonosobo District Senior High School. The research approach used is qualitative with qualitative descriptive method. Techniques of data collection using interviews, observation and documentation. Source of data obtained from nine State Senior High School in Wonosobo regency. Data were analyzed using Miles and Huberman model data analysis. The results showed that the implementation of the 2013 curriculum has not had an impact on the management of laboratories in SMA Negeri in Kabupaten Wonosobo, the laboratory is not an integral part of teaching and learning activities especially science subjects. The reason for the management of the laboratory has not been an integral part of the learning process is that all laboratory activities are handled directly by the teacher of the maple managers, the laboratory management is only handled by the teacher who served as head of the laboratory, the management performed by the head of the laboratory is limited to the administration, and the laboratory does not have the technician and laboran.